Exploring the Functions, Goals, Traits, and Principles of Elementary School Guidance: A Comprehensive Literature Review from Theory to Practice - Rahmi Rahmi; Jayanti Jayanti (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
This research aims to explore the implementation of guidance and counseling services in elementary schools, with a specific focus on SDN 01 Ulak Karang. Using a literature review method supported by field observation conducted on January 10, 2025, the study investigates how guidance activities support students' academic, emotional, and social development. The findings reveal that the school provides structured guidance services through group sessions, individual counseling, and career awareness activities. Group guidance helps students develop social skills such as cooperation and conflict resolution, while individual counseling addresses emotional and personal issues faced by students. Despite being at the elementary level, the school has also initiated basic career guidance to help students recognize their interests and potentials. However, challenges remain, including limited professional counselors and the integration of guidance into the academic curriculum. The study concludes that guidance services play a vital role in supporting the holistic development of students and should be strengthened through institutional support and teacher training. These services are essential in shaping students’ character, academic readiness, and emotional resilience from an early age.